Scintigraphic Evaluation of Osteoblastic Activity in Extraction Sockets Treated With Platelet-Rich Fibrin - ERCAN, FERİHA (W B SAUNDERS CO-ELSEVIER INC, 2010)
Purpose: To evaluate the effect of platelet-rich fibrin (PRF) on the early bone healing process with bone scintigraphy based on technetium-99m methylene diphosphonate uptake in third molar extraction sockets. Patients and Methods: Fourteen patients with bilaterally soft tissue impacted third mandibular molars were included in the study. The right and left impacted third molars were surgically extracted in the same session. PRF was randomly administered into one of the extraction sockets, whereas the contralateral sockets were left without treatment. Four weeks after surgery, scintigrams were obtained to evaluate scintigraphic differences between PRF-treated and non-PRF-treated sockets. After completion of the clinical study, PRF samples were evaluated by light and scanning electron microscopy. Results: The average increase in technetium-99m methylene diphosphonate uptake as an indication of enhanced bone healing did not differ significantly between PRF-treated and non-PRF-treated sockets 4 weeks postoperatively (P > .05). Abundant fibrin and inflammatory cells were observed by light microscopic examination of PRF samples. Scanning electron microscopic analysis of PRF revealed the existence of platelet aggregates in a fibrin network and crystalline particles on the outer surface of PRF Conclusions: PRF might not lead to enhanced bone healing in soft tissue impacted mandibular third molar extraction sockets 4 weeks after surgery. PRF exhibits the potential characteristics of an autologous fibrin matrix. However, whether the presence of crystal-like particles on the outer surface of PRF alters bone healing should be investigated further. (C) 2010 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 68:980-989, 2010
Keywords: GROWTH-FACTORS; TOOTH EXTRACTION; BONE-MATRIX; PRF; PLASMA; CELLS